Circumcision Tradition (Reconstruction of Knowledge From Circumcision Practice in Non-Muslim Men in Medan) - Dewantara Bangun; Lister Berutu (Indonesian Journal of Medical Anthropology, 2020)
This research aims to discuss non-Muslim men's knowledge about circumcision practices that have done both pieces of knowledge about the meaning of circumcision and how to circumcision. Besides, to know various reasons, they practice circumcision. The method used is an ethnographic method with in-depth observation and interview techniques, by jumping directly into the research field at Sunatan House and Dr. Pirngadi Hospital Medan. The result of the study is that non-Muslim men interpret circumcision as cutting the tip of the penis, which can clean the impurities attached to the end of the penis and avoid various diseases. While the reason they commit circumcision is categorized into two categories, namely health and culture.